(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The article considers the analytical methods used to optimize the linear structure design profile, according to the main criteria of optimality (minimization of working marks, minimum balance and land work, and the limit value of the design slope). An analytical design through the use of the methods of least squares and quadratic programming was considered. The authors developed and offered the methodology that can be used to balance the design marks of profile inflection points, taking into consideration the weighting factors of the working marks influence the balance of land works. The quadratic programming method has been proven to be efficient and useful when it is necessary to take into account additional optimization conditions regarding the sum of working marks and the marginal slope. Examples of analytical design of a longitudinal profile of a road section are introduced.